2012
DOI: 10.5539/jas.v4n5p1
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Several Rye Cultivars with Respect to Arabinoxylans and Extract Viscosity

Abstract: Arabinoxylans are considered as the major limiting factor for use of rye in animal feeding. In this study, four selected winter rye cultivars were grown at nine locations and tested for arabinoxylans including total (TAX), soluble (SAX) and insoluble fractions (IAX), extract viscosity, falling numbers and crude protein contents. Amounts of TAX ranged on average between 89 and 103 g/kg wholemeal flour, and the extract viscosity between 2.6 and 5.1 cSt. The extract viscosity was significantly correlated with fal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 22 publications
0
27
0
Order By: Relevance
“…As per H.-U. Jürgens et al [17], the total number of pentosans varied from 89 to 103 mg/g, and the extractable viscosity ranged from 2.6 to 5.1 centistokes (cSt).…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…As per H.-U. Jürgens et al [17], the total number of pentosans varied from 89 to 103 mg/g, and the extractable viscosity ranged from 2.6 to 5.1 centistokes (cSt).…”
mentioning
confidence: 70%
“…Two weeks after harvesting, the grain was ground using a Laboratory Mill 3100 (Perten Instruments, Germany), flour and meal were sampled as per State Standard GOST 13586.5-85. Pentosans were quantified by high-performance liquid chromatography in a HPLC-RI system (JASCO Deutschland GmbH, Germany) using a RF-10AXL fluorescent detector and 465 autosampler (Kontron Instruments, Germany) [17]. The qualitative composition of pentosans was evaluated according to the total number of arabinoxylans (total arabinoxylans, TAX) and the fraction of water-soluble arabinoxylans (soluble arabinoxylans, SAX).…”
mentioning
confidence: 99%
“…All grain crops contain anti-nutrients, but rye grain contains more anti-nutrient substances than does any other grain (Puztai 1967;Wieringa 1967). However, there are several advantages of cultivating rye, namely the low soil-quality requirements, tolerance for a wide range of climate conditions and high resistance to pests and moulds (Jürgens et al 2012). While rye cultivation is relatively inexpensive, the yields are typically as high as for other cereals (Bujak and Dopierała 2007;Hübner et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In the 1980s, several modern rye cultivars with significantly reduced alkylresorcinol concentrations had been developed (Hoffmann and Wenzel 1981), but despite these technological advancements, a number of studies still have shown suboptimal productivity in commercial herds of pigs receiving large quantities of the rye cultivars (Makarska et al 2007;Jurgens et al 2012). Therefore, in the early1990s, the importance of alkylresorcinols as a primary anti-nutrient was questioned, and more attention was devoted to other substances present in rye grain.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past several years, however, a number of new rye varieties with significantly reduced content of anti-nutritive substances have become available on the market (Makarska et al 2007;Jurgens et al 2012). Many of these new varieties have been tested as the primary feed ingredient (≥ 50% of total feed content) for fattener pigs in commercial operations (Hooper et al 2002;Schwarz et al 2015).…”
Section: Introductionmentioning
confidence: 99%